Environmentally sustainable apparel: recycle, repairing and reuse apparel - Kamis, Arasinah; Suhairom, Nornazira; Jamaluddin, Rahimah; Syamwil, Rodia; Ahmad Puad, Farah Najwa (2018)
This article intends to present information and awareness to the society regarding issues related the importance of recycling textile and apparels. This is mainly due to the fact that the fashion industry is among the ones that produce great quantity of waste that could lead to environmental pollution. Textile material waste is becoming a common issue in the fashion industry. This happens when drastic changes occur in the fashion industry. Thus, the fashion industry now produces various designs of apparels by offering low prices. Therefore, the consumers are presented with more choices in choosing their clothing style that needs to be disposed and recycled. Due to this, the textile and apparel production should take into consideration the importance of sustaining the environment by producing environment-friendly products that can be recycled. The fashion industry players need to think of effective methods that encourage consumers to buy textile products that can be recycled and re-used. Designers need to be creative and innovative in re-designing apparels which are being recycled. The consumers need to be more positive and show tendency to buy textile products and environment-friendly apparels that are made of used materials and organic materials such as bamboo, chicken feather fibre and vegetable oil. All the related parties need to work together in order to overcome environmental pollution and this cooperation will ensure proper and effective handling of environmental pollution.